Lupus-specific health outcome measure for US patients: the LupusQoL-US version. Issue 01 (6th January 2009) - Jolly, M; Pickard, A S; Wilke, C; Mikolaitis, R A; Teh, L-S; McElhone, K; Fogg, L; Block, J
Abstract : Background: Patient-reported outcomes are valuable for the management of chronic diseases like systematic lupus erythematosus (SLE), but no measures have been validated for use in US-based patients with SLE. Objectives: To adapt and assess the validity and reliability of an SLE-specific quality of life (QoL) measure developed in the United Kingdom, the LupusQoL, for use in US-based patients with SLE. Methods: Debriefing interviews of subjects with SLE guided the language modifications of the tool. The LupusQoL-US, SF-36 and EQ5D were administered. Internal consistency (ICR) and test–retest (TRT) reliability, convergent and discriminative validity were examined. Factor analyses were performed. Results: The mean (SD) age of the 185 subjects with SLE was 42.5 (12.9) years. ICR and TRT of the eight domains ranged from 0.85 to 0.94 and 0.68 to 0.92, respectively. Related domains on the SF-36 correlated with the LupusQoL domains (physical health and physical function r = 0.73, physical health and role physical r = 0.57, emotional health and mental health r = 0.72, emotional health and role emotional r = 0.48, pain and bodily pain r = 0.66, fatigue and vitality r = 0.70, planning and social functioning r = 0.58). Most LupusQoL-US domains could discriminate between subjects with varied disease activity and damage. Principal component analysis disclosed five factors in the US version, with physical function, pain and planning items loading on one factor. Conclusions: These data provide evidence to support the psychometric properties of the LupusQoL-US, suggesting its utility as an assessment tool for patients with SLE in the USA.